2002
DOI: 10.1128/jvi.76.12.5985-5992.2002
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus of Genotype B with or without Recombination with Genotype C over the Precore Region plus the Core Gene

Abstract: The entire nucleotide sequences of 70 hepatitis B virus (HBV) isolates of genotype B (HBV/B), including 38 newly determined and 32 retrieved from the international DNA database (DDBJ/EMBL/GenBank), were compared phylogenetically. Two subgroups of HBV/B were identified based on sequence divergence in the precore region plus the core gene, one with the recombination with genotype C and the other without it. The analysis over the entire genome of HBV/B by the SimPlot program located the recombination with genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
250
1
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 271 publications
(263 citation statements)
references
References 21 publications
9
250
1
2
Order By: Relevance
“…Similar to the study reported by Sugauchi et al (2002), a comparison of nucleotide similarities from positions 1814 to 2452 in the precore and core gene of the present five isolates from the Philippines and representative HBV/B isolates from the other four subgenotypes, B1-B4, with isolates from HBV/C and B1 is shown in Supplementary Table S1 in JGV Online. The divergences confirmed that HBV/B in the Philippines had recombined with HBV/C in the precore and core gene, like in B2, B3 and B4.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…Similar to the study reported by Sugauchi et al (2002), a comparison of nucleotide similarities from positions 1814 to 2452 in the precore and core gene of the present five isolates from the Philippines and representative HBV/B isolates from the other four subgenotypes, B1-B4, with isolates from HBV/C and B1 is shown in Supplementary Table S1 in JGV Online. The divergences confirmed that HBV/B in the Philippines had recombined with HBV/C in the precore and core gene, like in B2, B3 and B4.…”
supporting
confidence: 59%
“…Ba (B2, B3 and B4) has recombined with genotype C and has a higher prevalence of HBe antigen, so it manifests a more severe clinical course than Bj (B1) (Sugauchi et al, 2002). Thus, HBV needs to be examined with regards not only to its genotype, but also to its subgenotypes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This fact suggests different virologic, host, and environmental factors in patients with genotype B between Japan and Taiwan. Recently, Sugauchi et al 24 reported that there were virologic differences between HBV genotype B strains from Japanese and those from other Asian patients, including Taiwanese. 24 This may be a clue to explaining the inconsistent findings in HCC patients between Japan and Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…HBV subgenotype A1 appears to be associated with low serum HBV DNA levels as well as a low prevalence of serum HBeAg and is implicated in the high incidence of HBV-related HCC in Africa [61]; whereas subgenotype A2 has a higher rate of sustained remission after HBeAg seroconversion and a lower rate of liver-related death than other genotypes during long-term follow-up [62,63]. Sugauchi et al found that positivity of HBeAg is significantly more frequent in carriers of subgenotype B1 than B2 [64]. An additional study analyzed the distribution of HBV subgenotypes in 296 HBV-related HCC patients collected from all over Japan [65].…”
Section: Genotype and Subgenotypementioning
confidence: 99%